The Mediating Role of Orthorexia in the Relationship between Physical Activity and Fear of COVID-19 among University Students in Poland - Cezary Kuśnierz (MDPI AG, 2021)
Previous research showed that the COVID-19 pandemic has a significant impact on the wellbeing and lifestyle of populations worldwide, including eating and physical activity (PA) patterns. The present study aims to examine the mediating effect of orthorexia on the relationship between PA and fear of COVID-19. A sample of 473 university students from Poland of a mean age of 22 years (M = 22.04, SD = 2.90, 47% of women) participated in the cross-sectional online survey study. Continuous variables were measured using the Fear of COVID-19 Scale (FCV-19S) and the Test of Orthorexia Nervosa (TON-17), while categorical variables divided participants into the physically active and inactive group regarding WHO criteria (150 min per week). Weak gender differences were found. Active people showed lower fear of COVID-19 and higher orthorexia scores than those inactive. Orthorexia was found as a suppressor variable, which increases the negative predictive value of PA on fear of COVID-19. The model of cooperative suppression explained 7% of FCV-19S. The mechanism of mediation showed that health-related behavior could help reduce fear of COVID-19, but caution is necessary for people with addictive behavior tendencies. Universities should support university students by offering programs focused on increasing healthy lifestyles and improving wellbeing.